Odpowiedzi

2010-01-07T12:13:35+01:00
X =
(6 7/12- 3 1/36)*2,7 - 0,65:4 1/3 =
(79/12 - 109/36)*2,7 - 0,65*3/13 =
(237/36 - 109-36)*2,7 - 1,95/13 =
128/36*2,7 - 0,15 =
32/9*2,7 - 0,15 =
86,4/9 - 0,15 =
9,6 - 0,15 =
9,45

y =
(5 7/15 - 2 11/45)*3,6-10*1 1/5+2,5 =
(82/15 - 101/45)*3,6 - 10*1,2+2,5 =
(246/45 - 101/45)*3,6 - 14,5 =
145/45*3,6 - 14,5 =
522/45 - 14,5 =
11,6 - 14,5 =
-2,9

0,8 * (9,45 + (-2,9)) = 0,8 * 6,55 = 5,24
Najlepsza Odpowiedź!
2010-01-07T12:26:57+01:00
X=(6 7/12- 3 1/36)*2,7-0,65:4 1/3=(79/12 -109/36)*2,7-0,65:13/3=
(237/36 - 109/36)*2,7-13/20*3/13=128/36*2,7-3/20=
=32/9*2,7-3/20=32/9*27/10-3/20=48/5-3/20=9,6-0,15=9,45
y=(5 7/15 - 2 11/45)*3,6-10*1 1/5+2,5 =
=(82/15-101/45)*3,6-10*6/5+2,5=(246/45-101/45)*36/10-12+2,5=
=145/45*36/10-12+2,5=29/9*18/5-12+2,5=58/45-12+2,5=
=522/45-12+2,5=11,6-12+2,5=2,1
x+y=9,45+2,1=11,55
11,55*80%=11,55*0,8=9,24